UJI EFEKTIVITAS EKSTRAK SERASAH DAUN CENGKEH (Syzygium aromaticum L.) PADA KONSENTRASI BERBEDA TERHADAP PERTUMBUHAN JAMUR KULIT KEPALA - ., Ni Luh Komang Rai Touryantini; ., Dr. I Wayan Sukra Warpala,S.Pd,M.Sc; ., Dr. Ni Luh Putu Manik Widiyanti,S.Si,M (Jurnal Pendidikan Biologi undiksha, 2016)
Fungi is a normal flora that live on the human scalp, but when the amount of fungi is already past the normal limits of life on the scalp will cause infection. One of the plants that can be used as antifungal namely cloves (Syzygium aromaticum L.).The purposes of this research are (1) to knowing and describing the differences in zone diameter of constraints due to the provision of various concentration of extract of leaf litter clove (Syzygium aromaticum L.) (2) knowing and describing the extract concentration manure of clove leaves (Syzygium aromaticum L) which is effective in impeding the growth of fungal scalp, (3) knowing and describing the number of genus of fungi which was found in this research. This research was an experimental research which used Complete Random Design. The technique of data analysis was experiment and the data were analyzed by using one-way ANAVA statistic. The result of this research were (1) there was difference in zone diameter of constraints due to the provision as the effect of giving the variance of extract concentration manure of clove leaves (Syzygium aromaticum L), (2) the extract concentration manure of clove leaves (Syzygium aromaticum L) which was effective in impeding the growth of fungi caused scalp was 15% because it could impede the growth of fungi up to 79% and the effective concentration in killing the fungi was at the concentration 20 % because it could impede the growth of fungi up to 99,9%, and (3) the genus of fungi which was found in this research was Absidia, Aspergillus, Rhizopus, and Trichophyton.keyword : clove, effectiveness, fungi